The Influence of Price, Promotion, and Service Quality on Interest in Private Tutoring - Suryatnu, Alfandi Ovi Adam; Wardani, Dewi Kusuma; Octoria, Dini (Economic Education and Entrepreneurship Journal, 2023)
Tutoring plays an important role, especially for the development of student learning because not only the knowledge obtained at school but also student learning motivation. Even though currently the National Examination is abolished, students still have learning needs both classically in class and independently through tutoring. This study aims to find out and analyze the effect of price, promotion, service quality in the interest of following private tutoring both partially and simultaneously. This research is a quantitative research method with a population of 802 students in class XI at four private high schools in Central Java, Surakarta namely Regina Pacis High School, Al Abidin Bilingual Boarding School High School, Muhammadiyah High School Kottabarat Special Program, and Al Islam 1 Surakarta High School. The sampling technique use proportionate random sampling. Collect data use questionnaires and analysis of the data use is multiple linear regression analysisKeywords: Price, Promotion, Service Quality, Interest in Private TutoringDOI: http://dx.doi.org/10.23960/E3J/v6i1.56-64